2011
DOI: 10.3340/jkns.2011.50.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Nontraumatic Acute Spinal Subdural Hematoma

Abstract: 268hospital and was classified as grade 1. An examination found hypoesthesia at the T8 level and below and the deep tendon reflexes were reduced. We performed a chest computed tomography (CT) scan, but aortic dissection was not observed. We suspected hypokalemic periodic paralysis of both lower extremities and conducted laboratory studies; however, the results were negative. We then suspected thoracic myelopathy and thus provided steroid mega-dose therapy and conducted magnetic resonance imaging (MRI). The mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Therefore, low CSF pressure due to excessive surgical CSF drain age may have played an important role in the develop ment of spinal SDH. 15,26,43,46 Spinal SDH after craniotomy without intracranial SDH has also been reported. 15,23,26 Rader 32 suggested that a sudden increase in abdominal and thoracic pressure may rapidly elevate the pressure in the spinal vessels crossing the subdural and subarachnoid spaces and if CSF pressure fails to immediately buffer this force, vessel rupture may ensue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low CSF pressure due to excessive surgical CSF drain age may have played an important role in the develop ment of spinal SDH. 15,26,43,46 Spinal SDH after craniotomy without intracranial SDH has also been reported. 15,23,26 Rader 32 suggested that a sudden increase in abdominal and thoracic pressure may rapidly elevate the pressure in the spinal vessels crossing the subdural and subarachnoid spaces and if CSF pressure fails to immediately buffer this force, vessel rupture may ensue.…”
Section: Discussionmentioning
confidence: 99%
“…SSH is most often located in the thoracic region [16]. The etiopathogenic mechanisms involved in the constitution of SSH remains unclear [[17], [18], [19]]. In the subdural spinal space, there are no major blood vessels in contrast with the spinal epidural space or the intracranial subdural space [18].…”
Section: Discussionmentioning
confidence: 99%
“…Nontraumatic or spontaneous spinal hematomas are rare and are usually epidural in origin [ 10 ]. Spontaneous SSDH are extremely rare and are associated with numerous risk factors, such as iatrogenic causes (lumbar puncture, spinal anesthesia, and spinal surgery), bleeding disorders, spinal tumors, arteriovenous malformations, and OACs [ 10 13 ].…”
Section: Discussionmentioning
confidence: 99%